Building a halal MSME incubator in a heritage district: A qualitative single-case study of the Kauman Solo halal culinary area - Muhamad Iqbal Haqiqi Maramis; Asmen Junaidi Firman; Tika Widiastuti; Imron Mawardi; Mochammad Soleh (Journal of Halal Science and Research, 2026)
This study explores how the Kauman Solo Halal Culinary Area contributes to strengthening the halal ecosystem and improving the performance of MSMEs, as well as formulating an Islamic value-based incubation model. The approach used is qualitative phenomenological with a single case study design. Informants were selected purposively and through snowball sampling, including JPH regulators/authorities, area/community managers, MSME actors, and financial-philanthropy partners (Bank Syariah Indonesia as a distributor, Jamkrindo Syariah as a guarantor, and BAZNAS as a qardhul hasan supporter). Primary data were collected through semi-structured in-depth interviews (45–90 minutes in length), field observations, and document reviews; all informants provided informed consent and were anonymized. Data analysis followed the Miles & Huberman process (reduction–presentation–conclusion) with the help of NVivo 12 for thematic coding (open–axial) and node mapping. The validity of the findings was ensured through triangulation of sources and methods, limited member checking, and audit trails. The results show that: (i) the region encourages increased readiness for halal certification, digital adoption, and market access for MSMEs; (ii) the three-stage incubation model (pre-incubation–core–acceleration) effectively closes the capability gap; (iii) the region's collective financing scheme—a collaboration between BSI, Jamkrindo Syariah, and BAZNAS—accelerates inclusive capacity expansion. The study offers a conceptualization of the "Halal Heritage Hub" as a framework for replication in other regions, along with policy implications for strengthening the halal ecosystem. Keywords: Halal culinary area, Halal value chain, Islamic business model, Local economic development, MSME business incubation.